2014
DOI: 10.5204/jld.v7i2.201
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Student Success via Online Homework Usage

Abstract: With the amount of data available through an online homework system about students' study habits, it stands to reason that such systems can be used to identify likely student outcomes. A study was conducted to see how student usage of an online chemistry homework system, Online Web-based Learning (OWL) correlated with student success in a general chemistry course. Online chemistry homework activity was examined for first-year students taking general chemistry at a mid-size, private university. The six differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 19 publications
1
17
2
Order By: Relevance
“…This contradicts findings from previous studies that found web-based homework management systems to be associated with guessing behaviors, grade inflation, and superficial learning leading to poor exam performance (Bowman et al, 2014; Fatemi et al, 2015;Rhodes & Sarbaum, 2015). Neither guessing behaviors nor grade inflation was seen with the addition of the web-based homework management system in this study.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…This contradicts findings from previous studies that found web-based homework management systems to be associated with guessing behaviors, grade inflation, and superficial learning leading to poor exam performance (Bowman et al, 2014; Fatemi et al, 2015;Rhodes & Sarbaum, 2015). Neither guessing behaviors nor grade inflation was seen with the addition of the web-based homework management system in this study.…”
Section: Discussioncontrasting
confidence: 99%
“…The research showed that problem solving became unproductive after the first attempt, and that an increase in the allowed number of attempts was associated with a reduction in the homework completion rate. Bowman, Gulacar, and King (2014) also found that although there was a positive correlation between increased time spent on homework and use of the web-based homework management systems and exam scores, those results reversed when multiple attempts were allowed. Multiple attempts on homework questions correlated negatively with exam scores and student course grades.…”
Section: Literature Reviewmentioning
confidence: 92%
See 2 more Smart Citations
“…The large amounts of data generated by online learning systems provide researchers with ample opportunities to observe and measure various aspects of students' learning behavior, such as accessing learning resources [1][2][3], problem-solving [4][5][6][7], decision making [8], and engagement in online discussion [9,10]. There is a significant and rapidly growing body of research that examines the relationship between students' online learning behavior and course outcomes.…”
Section: Introductionmentioning
confidence: 99%